A framework for green manufacturing practicies in small and medium enterprises in Malaysia - Zakaria, Nur Syuhada (2018)
Green Manufacturing Practices (GrMP) is a term used to describe manufacturing practices that do not harm the environment during any part of the manufacturing process. It emphasizes the use of processes that do not pollute the environment or harm consumers, employees, or other members of the community. Small and medium enterprises (SMEs) are moving toward sustainable alternatives through GrMP method. It stresses on critical factors such as organisational style, eco-knowledge, business environment, society influences, supply chain management and technology network. Large size industries are more compelled to do so compared to SMEs due to the fact that they are more influential with better organizational management and good financial stability compared to SMEs. However, SMEs are trying to adapt GrMP as a mandatory process, but lack of proper framework which guide them for implementation. Therefore, this study developes the framework of GrMP for local SMEs. The study involves enablers and barriers in implementing GrMP from previous literatures. This work formulate a framework based on relationship between criticals factors with enablers and barriers. 59 of respondents from local industries in Malaysia were selected as respondents based on six of critical factors divided into two parts which are enablers and barriers. The questionnaire are designed based on this. Survey were evaluated by using Statistical Package for the Social Sciences (SPSS) version 23, in terms of correlation, reliability, central tendency and variability testing. The finding on this study in the term of framework will help SMEs to implementing GrMP. Framework formulate relates the critical factors from previous literature and enablers and barriers from survey based on perception of industries expert. GrMP for SMEs are the first step of environmental awareness and ecological responsibilties.